The Effect of Gender Stereotyping on Career Choices Among Girls in Secondary Schools in Uganda: A Case of St. John’s High School Mukono - Ivy Stacy Nambi (Uganda Christian University, 2024)
The study examined the effect of gender stereotyping on career choices among girls in secondary schools in Uganda: a case of St John’s High School Mukono. It specifically focused on; assessing the influence of family influence on career choice among girls, establishing the influence of occupational stereotypes on career choice among girls and examining the influence of exposure to mass media on career choice among girls at St Johns high school. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and simple random sampling methods were used. A sample size of 136 respondents who are S.4, S.5 & S.6 from St Johns High School-Mukono was selected although 120 of them responded to the study. The key informants included the head teacher, teachers, school counselor and senior woman. The study revealed that on average, 70% of the respondents agreed that gender stereotyping, including family influence, occupational stereotypes, and exposure to mass media, significantly affects career choices among girls at St. John's High School. Pearson’s correlation analysis shows strong positive relationships between family influence (r = .744, p < .05), occupational stereotypes (r = .639, p < .05), and exposure to mass media (r = .711, p < .05) with career choices. Regression analysis reveals that these factors explain 63.1% of the variations in career choices with family influence (β = .412), occupational stereotypes (β = .322), and mass media exposure (β = .225) all contributing significantly to improving career choices among girls. Lastly, the study recommended the need for families to promote open discussions about diverse career paths for girls, free from traditional gender expectations. The study also recommended the need for schools to actively challenge occupational stereotypes by incorporating gender-sensitive career guidance programs. Finally, the study recommended the need for critical media literacy programs in secondary schools to help female students critically assess media portrayals of gender roles and careers.